مظاهر التكريم الإلهي للنفس الإنسانية - عباس، رامي سامي ضيف الله; خطاطبة، عدنان مصطفى إبراهيم (جامعة القدس المفتوحة, 2016)
هدفت هذه الدراسة إلى بيان مظاهر التكريم الإلهي لنفس الإنسانية، واتبعت الدراسة المنهج الوصفي والمنهج الاستقرائي الاستنباطي، وهي من أهم النتائج التي توصلت إليها هذه الدارسة. أولاً: مظاهر التكريم الإلهي للنفس الإنسانية في السماء واهمها الاتي: إعلان نبأ أدم خلق ادم عليه السلام من الله تعالي مباشرة، وخلق الله عز وجل سيدنا أدم عليه السلام بيده ونخ فيه من روحه، وأمر الله عز وجل الملائكة بالسجود لسيدنا ادم علية السلام وسكون أدم عليه السلام في الجنة مع انه مخلوق ليكون خليفة في الأرض. ثانياً: مظاهر التكريم الإلهي للنفس الإنسانية في الأرض، واهمها الاتي: تسخير كل ما في السماء والأرض للإنسان، وتفضيل الإنسان على سائر المخلوقات، وتشريع الأحكام التي تحقق مصلحة ومنعه الإنسان، وإرسال الرسل وإنزال الكتب السماوية، وجعل الإنسان خليفة في الأرض وتزويده باستعدادات الخلافة الخاصة به.
The objective of the study was to identify the aspects of Divine honoring for the human soul. The study used the descriptive inductive deductive design. The most important results of the study were: .First: The aspects of Divine honoring in heaven, and these include the following: The declaration of Adam creation by God as God created our father Adam with His own hands, and blows his spirit from His own spirit, ordered angles to glorify Adam and the residence of Adam in Heaven although he was one of God's creatures to be his decedent on Earth. .Second: The aspects of divine honoring of humans on Earth: And these include the following: Dedicating all things on Earth and sky in the service of man, preferring man on other creatures, putting judgments and rules that benefit man, sending messengers and prophets and holy books, making man God's decedent on Earth and providing him with all the needed potentials.
Keywords: النفس الإنسانية -- التكريم الإلهي